Standardized Xylocarpus moluccensis fruit fraction mitigates collagen-induced arthritis in mice by regulating immune response. (9th February 2020) - Gupta, Priya; Kumar, Amit; Pal, Subhashis; Kumar, Sachin; Lahiri, Amit; Kumaravelu, Jagavelu; Chattopadhyay, Naibedya; Dikshit, Madhu; Barthwal, Manoj Kumar
Abstract: Objective: This study was undertaken to evaluate the effect of Xylocarpus moluccensis fruit fraction (F018) on the pathogenesis of collagen-induced arthritis in mice. Methods: Arthritis was induced by intradermal injection of collagen (2 mg/ml) with complete Freund's adjuvant in DBA/1J mice. F018 was administered orally at 1, 3 and 10 mg/kg for 20 days. Disease progression and mechanism were assessed by micro-CT analysis, RT-PCR, flow cytometry assay, myeloperoxidase (MPO) and MTT assay. Results: F018 at 3 and 10 mg/kg significantly reduced paw thickness, clinical score, mononuclear cell infiltration and collagen layer depletion in the knee section of collagen-induced arthritis (CIA) mice when compared with collagen-induced arthritis mice alone. Furthermore, F018 treatment in collagen-induced arthritis mice significantly recovered bone volume and trabecular number and decreased the trabecular space by modulating RANKL and OPG mRNA expression in the synovial tissue. F018 treatment in collagen-induced arthritis mice significantly attenuated spleen index, lymphocyte proliferation and paw myeloperoxidase (MPO) activity, pro-inflammatory cytokine TNFα, IL1β, and IL6 mRNA expression and enhanced IL10 mRNA expression in paw tissue. Furthermore, F018 treatment in collagen-induced arthritis mice significantly reduced splenic dendritic cell maturation and Th17 cells. In culture, F018 significantly decreased collagen-induced arthritis-FLS proliferation and promoted apoptosis. Conclusion: F018 may serve as a potential curative agent for arthritis.